Adsorption of mercury from water by modified multi-walled carbon nanotubes adsorption behaviour and interference resistance by coexisting anions - Chen, Paris Honglay (Environmental technology, 2014)
This investigation reports the use of modified multi-walled carbon nanotubes (MWCNTs) with various functional groups for adsorbing inorganic divalent mercury (Hg(II)) from water samples. To elucidate the behaviours and mechanisms of Hg(II) adsorption by modified MWCNTs, their adsorption capacity was studied by considering adsorption isotherms and kinetics. Particular attention was paid to interference of coexisting inorganic ions with Hg(II) adsorption. The results reveal that functionalization with oxygen-containing groups improved the Hg(II) adsorption capacity of the MWCNTs. Kinetic analysis demonstrated that the adsorption of Hg(II) by MWCNTs was closely described by the pseudo-second-order and Elovich models, suggesting that the adsorption of Hg(II) by MWCNTs was significantly affected by chemical adsorption. The kinetic results were also analysed using the intraparticle diffusion model, which revealed that intraparticle diffusion was not the only rate-controlling mechanism. The adsorption of Hg(II) on MWCNTs fell drastically as the ionic strength increased from 0 to 1.0mol/L chloride ions, and declined significantly as the pH increased from 2.2 to 10.5. The elemental maps obtained by energy-dispersive spectrometer (EDS) revealed the formation of surface complexes of chloride ions with functional groups on MWCNTs, which reduced the number of available sites for the adsorption of Hg(II) and strengthened the repulsive forces between Hg(II) and MWCNTs. The EDS results suggest that chloride ions are important in controlling Hg(II) speciation and adsorption on the surfaces of MWCNTs